An Account of Geographic Concentration Patterns in Europe - Marius Brülhart; Rolf Traeger (European Regional Science Association (ERSA), 2003)
Using entropy indices and associated bootstrap tests, we describe the distribution of economic sectors across Western European regions over the 1975-2000 period. We decompose sectoral concentration into its within-country and between-country components In addition, we estimate centre-periphery gradients in sectoral location patterns and the impact of EU membership on countries' internal geography. It is found that manufacturing has become gradually more concentrated, although the locational bias towards central locations has become weaker. EU membership has significantly strengthened countries' internal concentration trends in manufacturing as well as market services.
Keywords: 330